Apple Watch For Dummies, 3rd Edition - Saltzman, Marc (--For dummies., 2019)
Get connected with Apple Watch The new and improved Apple Watch does it all-tells time, tracks your fitness, monitors your health, keeps you connected, and so much more! Apple Watch for Dummies covers the latest series and version of Apple Watch, giving you the lowdown on the new WatchOS. You'll learn how to use all the exciting new features, watch faces, improvements to Siri, and how to customize your Apple Watch to suit your needs! From picking the right watch model and learning the "newbie" basics to must-have apps, troubleshooting, and beyond, this book will help you wrap your head around the Apple Watch! Send and receive text message and e-mails Use Siri to control Apple Watch with your voice Taking advantage of advanced health and fitness features Adjust Apple Watch settings to meet your needs Push Apple Watch to its limits with advanced techniques Whether you're a beginner or already an Apple Watch veteran, read this book to get a handle on all the features and tools of the latest and greatest Apple Watch.